Photographic Durations - Documenting Snippets of My Nana's Life - Pittwood, Katey Marie (Auckland University of Technology, 2011)
This visual arts research project will explore my Nana’s daily rituals through analogue photographic investigations. It aims to explore the relationship between photography and the desire for nostalgic experiences, specifically focusing on the compulsive desire to protect and photograph what is at risk of becoming lost. This practical project examines the relationship between mortality and photography. It takes into consideration preconceptions and emotive reactions that exist in western culture towards the notion of loss and how we deal with this. It questions whether photography enables us to come closer to addressing mortality and death. This project will be explored from an autobiographical standpoint, through the documentation of the personal and familial connection between my Nana and myself. This project attempts to non-invasively capture small but distinctive moments of Nana’s life in her domestic space. Driven by the desire to ‘preserve’ these moments, her day-to-day rituals will be investigated through regular, routine visits in order to explore multi-faceted collections and create an accumulative narrative. The project aims to represent the routine nature of this repeated process in a way that celebrates the specific way I as both photographer and granddaughter relate to and observe her as my Nana by the way of weekly visits.
Keywords: Loss; Nostalgia; Photography; Duration; Ritual; Memories